PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN LKPD TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI GERAK MELINGKAR - Nurwulandari, Nira (ScienceEdu, 2024)
This research aims to evaluate the effectiveness of applying the Problem Based Learning (PBL) model assisted by Student Worksheets (LKPD) on students' critical thinking abilities in circular motion material. The research method used was quantitative with a quasi-experimental design, involving two groups. The research population was class X students in one of the high schools, with samples taken by purposive sampling consisting of two homogeneous classes. The instruments used include validated critical thinking ability tests, LKPD, observations, and interviews. Critical thinking ability tests were carried out before (pre-test) and after (post-test) treatment. The results showed that the average pre-test score for the experimental group was 65 and post-test was 80, while in the control group, the average pre-test score was 63 and post-test was 70. Data analysis used the independent t-test. showed a significant difference between the increase in critical thinking skills in the experimental group and the control group (p < 0.05). The results of this research indicate that the PBL model assisted by LKPD is significantly more effective in improving students' critical thinking skills compared to conventional learning methods. LKPD helps students follow PBL steps in a more structured manner and encourages active and collaborative involvement. The implication of this research is the need to integrate PBL and LKPD models in the learning curriculum to improve the quality of education and students' critical thinking abilities. This research also suggests training and support for teachers in implementing the PBL model.